CHRONIC ILLNESS AND IDENTITY: SOCIAL IDENTITY IN OLDER BLACK MALES AGING WITH CHRONIC ILLNESS. (11th November 2018) - Atakere, D; Baker, T
Abstract: Research suggests that chronic illness challenges how individuals view themselves and their role in society/their community. In this study, we examined how older Black males reconstruct their masculinity following diagnoses with chronic illness(es). For a holistic understanding of the lived experiences of older Black males with chronic illness, life history interviews were conducted among Black males aged 55 to 65 years of age. Results suggest that chronic illness violates understandings of what it means to be a man. The men noted that chronic illness influences their sense of safety, sexual encounters, duties and obligations, and choice of intimate partners. Participants agreed that chronic illness alters there current identity, because "they have to negotiate, define and redefine their Black male identity." Others responded that they "struggle to reconcile becoming an older adult and having a chronic illness, and renegotiating what it feels [like] to be a man." Data further showed that the men are aware of the identity dynamics that buffer their exclusion from the dominant Black male culture and hinders their opportunity and desire to identify with contemporary Black masculine cultures. By focusing attention on Black males with chronic illness, this research shows the complexity involved in identity formation in older adults – illustrating how certain aspects of their identities become salient over time. Our findings provide arguments for culturally targeted and culturally tailored geriatric support and services.